Pyrolytic Product Distribution Analysis on Co-Pyrolysis of Face Mask Waste and Lignocellulosic Waste - Mahendra, Rain Agri (Department of Mechanical Engineering, Universitas Andalas, 2023)
COVID-19 causes a large increase in medical and non-medical waste in the world, especially in developing countries. Improper waste management causes significant health problems and impacts on the environment. Pyrolysis is a process that utilizes thermal instability of organic components in waste to convert them into liquid (oil), solid (charcoal), gas and wax products that have potential as fuels. Co-pyrolysis of medical face masks as infectious medical waste with non-infectious medical waste such as food waste, garden waste and paper were investigated for energy valorization. Particles, temperature, nitrogen flow rate and waste characterization affected the resulting product. Pyrolysis was carried out at 400 Â°C with nitrogen (N2) flow rate of 0.5 L/min. Co-pyrolysis of face masks and food waste produced oil with the highest yield because food waste contains dominant amount of cellulose and hemicellulose promoting high oil yield. This pyrolysis method is considered a simple, clean, safe and effective technique to reduce the amount of waste during a global pandemic.